FAKTOR-FAKTOR YANG MEMENGARUHI KELAHIRAN PREMATUR DI INDONESIA: ANALISIS DATA RISKESDAS 2013 - Sulistiarini, Dwi; Berliana, Sarni Maniar (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Prematuritas is the second leading cause of death in babies after pneumonia and is the leading cause of neonatal mortality. Thirty-five percent of the world's neonatal death was caused by complications of premature birth (WHO: 2012). The purpose of this research is to know the characteristics of the sosiodemografi affect the incidence of premature birth in Indonesia. This research uses data Basic Health Research (Riskesdas) 2013. The unit of analysis in this research is the whole live births that occurred from January 2010 to June 2013. Binary logistic regression methods were used to figure out the tendencies of a woman experiencing premature birth events. The results showed that out of the 36% of females there 48336 mother who experienced premature birth. Logistic regression results indicate that all free variables used are significantly affecting the incidence of preterm birth. Women with childbirth when young age characteristics, lower-educated, living in rural areas, do not have a history of miscarriage, gave birth to their first child, do not do the complete pregnancy examination, and experienced complications while pregnant tend to be greater risk experienced premature birth. The last three factors give the greatest influence on the incidence of preterm birth, It is recommended that appropriate recommendations for pregnancy examinations program should be further promoted and qualified health care personnel and facilities should be available in all regions of Indonesia, especially in rural areas.